2013
DOI: 10.1097/ico.0b013e318271fc99
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Visual Acuity and Lamellar Thickness in Descemet Stripping Automated Endothelial Keratoplasty

Abstract: GT decreased after transplantation; however, there was a poor correlation of visual acuity with preoperative or postoperative DSAEK GT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…4,9,16 In DSAEK, endothelial graft thickness has been suggested as a factor that influences visual results. 8,10,11,[17][18][19][20][21] To date, there has been no randomized controlled trial to assess the effect of DSAEK graft thickness on visual acuity; however, the preliminary report of such a trial seems to suggest a favorable outcome toward thin DSAEKs. 22 Thin DSAEK techniques seem to offer better visual results compared with conventional DSAEK with graft thickness above 130 mm.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…4,9,16 In DSAEK, endothelial graft thickness has been suggested as a factor that influences visual results. 8,10,11,[17][18][19][20][21] To date, there has been no randomized controlled trial to assess the effect of DSAEK graft thickness on visual acuity; however, the preliminary report of such a trial seems to suggest a favorable outcome toward thin DSAEKs. 22 Thin DSAEK techniques seem to offer better visual results compared with conventional DSAEK with graft thickness above 130 mm.…”
Section: Discussionmentioning
confidence: 91%
“…1,[3][4][5] Although isolated transplantation of Descemet membrane and endothelium in Descemet membrane endothelial keratoplasty (DMEK) has shown superior visual outcomes, the technique is currently limited by surgical complexity in graft preparation and handling with an increased detachment rate. 3,[6][7][8] On the contrary, thin DSAEK offers technical advantages of conventional DSAEK while improving on visual outcomes. [8][9][10][11] Current thin DSAEK techniques include the use of 2 specialized microkeratome passes (ultrathin DSAEK) or, a femtosecond laser with or without a microkeratome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Corneal thickness and haze did not offer an adequate explanation for the decreased visual quality either [50]. Woodward et al studied the relationship of visual acuity and lamellar thickness in sixty-four eyes of 52 patients with a mean followup of 27 ± 16 months who underwent DSEK and concluded that there was a poor correlation between visual acuity with preoperative or postoperative DSAEK graft thickness [51]. …”
Section: Posterior Lamellar Keratoplasty or Endothelial Keratoplasmentioning
confidence: 99%
“…For example, there is some evidence that EK graft morphology may correlate with postoperative refractive error. 1,2 The effect of EK thickness on postoperative bestcorrected visual acuity is unknown; some studies found no correlation, [3][4][5][6][7] whereas others have demonstrated improved best-corrected visual acuity in patients with thinner postoperative graft measurements. 8,9 As eye banks and clinicians pursue creating symmetric and thin EK tissue, accurate measurements of donor tissue are critical for valid analysis.…”
mentioning
confidence: 97%